Identification and Assay of Isoniazid and Pyrazinamide in Fixed-Dose Dispersible Tablets Containing Rifampicin Using High-Performance Liquid Chromatography - Citra Santikasari; Meyliana Wulandari; Shofi Nafisa Ulfa; Mirawati Siregar; Syed Azhar Syed Sulaiman (Jurnal Riset Sains dan Kimia Terapan, 2025)
Tuberculosis (TB) remains a major global health challenge, particularly in Indonesia, which ranks among the countries withthe highest TB burden. Fixed-dose dispersible anti-tuberculosis formulations containing rifampicin, isoniazid, and pyrazinamide are widely recommended to enhance patient adherence and minimize the risk of drug resistance. Ensuring the quality and appropriate dosage of active pharmaceutical ingredients is essential for achieving therapeutic effectiveness and maintaining TB control. This study aimed to perform routine quality assessment and regulatory compliance assays on commercialanti-TB fixed-dose combination (FDC) dispersible tablets using a reversed-phase high-performance liquid chromatography (HPLC) method as specified in the International Pharmacopoeia 2025. The HPLC system was equipped with a C18 column and used a mobile phase consisting of acetate buffer (pH 5) and methanol (94:6 v/v). System suitability testing was conducted before analysis, with %RSD values below 2%, resolution greaterthan 2.0, and tailing factors ≤ 2.0, indicating acceptable precision, selectivity, and chromatographic performance. The retention times of isoniazid and pyrazinamide were consistent with those of the reference standards, confirming identity. The assay results showed that pyrazinamide (100.3%) and isoniazid (99.9%) were within the specification limits set by the International Pharmacopoeia. These findings demonstrate that the official monograph method is suitable for regulatory-grade quality control testing of dispersible anti-tuberculosis fixed-dose combination tablets, and that the tested product met pharmacopeial quality requirements.